The impact of digital technologies on economic and environmental performance in the context of industry 4.0: A moderated mediation model - Li, Ying; Dai, Jing; Cui, Li (International journal of production economics, 2020)
Digital technologies for Industry 4.0, such as the Internet of Things, cloud computing, big data and analytics, have attracted much attention from both researchers and practitioners. Based on information processing theory, this study intends to explore how digital technologies influence economic and environmental performance in the new era of Industry 4.0. The mediating effect of digital supply chain platforms and the moderating effect of environmental dynamism are proposed and evaluated using a survey of Chinese manufacturing firms. The results indicate that digital supply chain platforms mediate the effects of digital technologies on both economic and environmental performance and that the mediating effects are enhanced under a high degree of environmental dynamism. This study offers an enhanced understanding of the performance implications of digital technologies and provides managerial insights into how to promote economic and environmental sustainability in the era of Industry 4.0.